Urban health challenges in India – lessons learned from a surveillance study in Pune - Kroll, Mareike; Phalkey, Revati; Dutta, Sayani; Bharucha, Erach; Butsch, Carsten; Kraas, Frauke (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
Urban health in India is gaining increasing attention due to the growing share of urban population and the changing living conditions caused by the rapid urbanization process. The rising prevalence of non-communicable diseases (NCDs) such as diabetes is partly attributed to this process making NCD prevention and control one of the biggest public health challenges in the 21th century. Though public health programs in India are increasingly targeting NCDs, data quality and availability to budget scarce resources remains a challenge. The objective of the study was to conceptualize a prototype for an urban NCD sentinel surveillance system to capture data on newly diagnosed NCD cases, taking also into account socio-spatial intraurban differences. As preliminary steps, two systematic literature reviews, mapping of healthcare providers and a knowledge attitude practice survey on disease surveillance were conducted. In total, 258 private primary healthcare providers (allopathy, ayurveda, homeopathy and unani) participated in the survey, out of these 127 agreed to participate in the six months surveillance study, providing data on a monthly basis. The study indicates that, despite the small size and low level of infrastructure in the private clinics, these practitioners play an important role in diagnosing and treating NCDs. They can be involved in NCD surveillance, if the following major barriers are addressed: lack of regulation of the private sector, cross-practices among different systems of medicine, limited clinic infrastructure, and knowledge gaps about disease surveillance. Based on our findings, a voluntary augmented sentinel NCD surveillance system including public and private healthcare facilities at all levels of care might be an adequate approach to monitor NCD related health trends.